A GESTÃO DO TERRITÓRIO DO MUNICÍPIO DE MADRE DE DEUS-BA E SUA SUSTENTABILIDADE SÓCIO INSTITUCIONAL - Matos, Silvania Magliano (2006)
This research aims to understand the spatial distribution through the approach and social function of the space, analyzing and reflecting about the petroleum activities and the limits that those activities impose to the territory as a whole. It tries to understand how actions are engendered in the force field known as Madre de Deus municipal district. Although, the presence of Petrobrás in the Madre de Deus territory results in progress and local dynamism for it is known as a world reference, it is also true that Petrobrás puts pressure in the local job market in a retracted manner, for the local population is not being absorbed in this industrial reality. On the other hand, the Prefeitura Municipal de Madre de Deus/ Madre de Deus Municipal Mayor Office acts as an agent that makes possible the physical occupation of this territory. Madre de Deus Municipal Mayor Office adopts an urban managing that makes it viable the local development through infra-structure improvement, but ends up missing relevant actions that could change in a significant way the local life quality. It is important to emphasize that Madre de Deus is a territory with strategic position and its geopolitics is very important to Bahia s regional development. It represents an important axis inside of the Petrobrás industrial system. It has exceptional port facilities in the Baía de Todos os Santos/ All Saints Bay , as well as, a rich social-environment (swamp and marine ecosystem) and economy if we consider the receiving of royalties from Transpetro. On the other side of this geopolitical and physical distribution, we have a society completely dispersed from concrete social processes in an extent given to the low employment rate found in this municipal district, in the other extent given to the low associative capacity of the local population. Given that, how can we engender strategies in order to obtain a socialinstitutional sustainability to the diverse and complex Madre de Deus ?